Update on the Current Landscape of Transcatheter Options for Tricuspid Regurgitation Treatment - Jonathan Curio; Ozan M Demir; Matteo Pagnesi; Antonio Mangieri; Francesco Giannini; Giora Weisz; Azeem Latib (Interventional Cardiology: Reviews, Research, Resources)
Most patients with severe tricuspid regurgitation lack treatment options because of prohibitive surgical risk. New transcatheter treatments under development and investigation might be able to address this unmet clinical need. This article gives an update on the landscape of devices for transcatheter tricuspid regurgitation treatment including different approaches (i.e. repair with leaflet approximation or annuloplasty and replacement using orthotopic or heterotopic valves) at different stages of development, from experimental to clinical trial. Repair devices such as the Cardioband or the MitraClip are leading the field with promising preliminary data and further trials are ongoing. However, with implantations of the Gate bioprosthesis, replacement devices are catching up. Potential advantages of different approaches and most recent data are discussed.